The Okomu Forest Reserve in the Niger Delta Region of Nigeria: Evaluating its Services to Ecosystem and Small Holder Crop Farmers - OROKA, Frank; UREIGHO, Nelly (Kastamonu University, 2021)
Aim of study: The basis for sustainable conservation of any protected forest area is determined by the services it provides to the ecosystem and immediate communities. This study seeks to evaluate the services provided by the Okomu Forest Reserve that should warrant its conservation. Area of study: The study was conducted in Okomu Forest Reserve in Edo State, Southern Nigeria. The major practices of farmers in the surrounding communities are sole cassava and intercropping cassava with maize, melon and groundnut. Material and methods: The function system was used to evaluate the Okomu Forest Reserve, using a questionnaire containing a checklist of ecosystem functions. Respondents for the rural survey were crop farmers, while the urban survey were tourists from urban centres. Main results: Results showed that rural dwellers' important functions were food/nutrition, fuel energy, and fishing with mean values of 2.81, 2.49 and 2.04 respectively, while the urban dwellers’ important functions were recreation/tourism, educational/scientific information and nature protection with mean values of 2.82, 2.76 and 2.72 respectively. Highlights: The order of importance of forest functions as perceived by the urban respondents from the highest was carrier, information, regulation and least with production. The rural dwellers' perception from the highest was carrier, production and information functions as least.
Keywords: Okomu Orman Koruma Alanı; Ekosistem Fonksiyonları; Nijerya; Okomu Forest Reserve; Ecosystem Functions; Nigeria; 2. Zero hunger; 8. Economic growth; 11. Sustainability; 15. Life on land; 12. Responsible consumption